ZLN005 improves the survival of polymicrobial sepsis by increasing the bacterial killing via inducing lysosomal acidification and biogenesis in phagocytes - Suzuki, Yosuke; Kami, Daisuke; Taya, Toshihiko; Sano, Arata; Ogata, Takehiro; Matoba, Satoaki; Gojo, Satoshi (Frontiers in Immunology, 2023)
Polymicrobial sepsis still has a high mortality rate despite the development of antimicrobial agents, elaborate strategies to protect major organs, and the investment of numerous medical resources. Mitochondrial dysfunction, which acts as the center of energy metabolism, is clearly the basis of pathogenesis. Drugs that act on PGC1α, the master regulator of mitochondrial biosynthesis, have shown useful effects in the treatment of sepsis; therefore, we investigated the efficacy of ZLN005, a PGC1α agonist, and found significant improvement in overall survival in an animal model. The mode of action of this effect was examined, and it was shown that the respiratory capacity of mitochondria was enhanced immediately after administration and that the function of TFEB, a transcriptional regulator that promotes lysosome biosynthesis and mutually enhances PGC1α, was enhanced, as was the physical contact between mitochondria and lysosomes. ZLN005 strongly supported immune defense in early sepsis by increasing lysosome volume and acidity and enhancing cargo degradation, resulting in a significant reduction in bacterial load. ZLN005 rapidly acted on two organelles, mitochondria and lysosomes, against sepsis and interactively linked the two to improve the pathogenesis. This is the first demonstration that acidification of lysosomes by a small molecule is a mechanism of action in the therapeutic strategy for sepsis, which will have a significant impact on future drug discovery.